The Eeffect of Low Power Laser Radiation on Gingival Wound Healing - AR Takzaree; K Yarmohammadi; N Takzaree; H Semiyari; M Akbari (Tehran University of Medical Sciences, 2002)
Pain reduction and surgical wound healing enhancement have several advantages. Wound healing is a complex and organized phenomenon. During this phenomenon, definite and harmonized processes such as: reconstruction, immigration parenchyma and connective tissue cells proliferation and re-construction of gingival connective tissue take place. Studies show that lower power laser (He-Ne) can induce different biological changes in ceils through biochemical mechanisms. Considering the therapeutic effects of (He-Ne) low power laser radiation on healing processes, cell proliferation, connective tissue fibers and finally the acceleration of gingival wound healing were studied. This study was done on 50 mature and healthy rats with the average weight of 250 to 300 grams, and 3 to 4 months old. After anesthesia, maxillary wounds, with the same size, were made in all samples and they were randomly divided into control and test groups. After surgery, rats of test group received laser radiation with the value of 5 mJ/cm3 every day for a period of 5 days. And on the 5lh day, they were killed. Gingival biopsy was performed and histological study was done. The number of fibroblasts, collagens, endothelial ceils and blood vessels were counted. In test group, the granulation tissue was more active and the edema and inflammation were lesser than those of the control group. Data were analyzed by t-test method and PO.05 was significant. So, it is concluded that periodical radiation of (He-Ne) low power laser has an important role on surgical gingival wounds.